The specifics and development trends of internet intermediaries’ liability - Hovhannisyan, Arpine (Bulletin of Yerevan University C: Jurisprudence, 2025)
In recent years, the issue of the liability regime of internet intermediaries has become a central topic of discussion within the European legal and policy context. A particularly pressing question has emerged as to whether online platforms should bear legal responsibility in situations where their infrastructure is used to disseminate insults, defamation, hate speech, or other forms of content violating fundamental human rights. This issue becomes especially pronounced when individuals whose rights have been infringed address these platforms with formal requests to remove offensive or defamatory material, yet the platforms fail to act. Such situations raise the question of two-layered (or dual) liability, which involves not only the original authors of the unlawful content but also the intermediaries who enable its publication and continued accessibility. The relevance of this topic increased significantly after 2016, particularly in the context of several presidential elections and the Brexit referendum in the United Kingdom. These developments intensified public debates around the balance between freedom of expression and regulatory control over the information environment. Currently, the European Court of Human Rights has developed an almost consolidated body of case law, indicating that internet intermediaries may be held liable when they fail to take appropriate and timely measures to remove defamatory or offensive content from their platforms upon notification. This debate and its potential regulatory solutions are also highly relevant to the Armenian legal context, particularly in light of ongoing legislative reforms and the provisions of the Constitutional Court of Armenia’s decision of October 1 of the previous year. These developments are likely to play a decisive role in shaping the future regulatory framework for the liability of internet intermediaries in Armenia.